EFFECT OF GIBBERELIC ACID CONCENTRATION AND SOAKING PERIODS ON SEED GERMINATION AND SEEDLING GROWTH OF Pinus canariensis - Sumood H. Ali (Mesopotamia Journal of Agriculture)
This study was carried out during 2001 to investigate the effects of soaking of Pinus canariensis seeds in different concentration of GA3 (0,200and300) ppm for different periods (0,10,15and20) minutes. Results revealed the superiority of the concentration 300 ppm in all studied characters Vis; germination percentage , survival percentage , seedlings hight and dry weight of stem , leaves & roots . Also,the soaking period of 20 minutes showed superior result due to its effect on seedling hight and dry weight of stem and leaves . As well, the interaction of soaking in the concentration 300 ppm for 20 minutes was superior in its effect on the characters of dry weight of stems& leaves .